2010
DOI: 10.1068/p6712
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving Affordances for Joint Actions

Abstract: Two individuals acting together to achieve a shared goal often have an emergent set of afforded behavioral possibilities that may not easily reduce to either acting alone. In a series of experiments we examined the critical boundaries for transitions in behavior for individuals walking through an aperture alone or alongside another actor as a dyad. Results from experiment 1 indicated that an intrinsically scaled critical boundary for behavioral transitions was different in individuals than in dyads performing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…The findings in the present study are at least in part consistent with those from previous studies [1], [2], [4], [8], [9], [10], [17] in that the amplitude of shoulder rotations was proportioned to the critical ratio value. The new finding was that the amplitude of rotations was smaller for the respective ratio value as bar length increased.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings in the present study are at least in part consistent with those from previous studies [1], [2], [4], [8], [9], [10], [17] in that the amplitude of shoulder rotations was proportioned to the critical ratio value. The new finding was that the amplitude of rotations was smaller for the respective ratio value as bar length increased.…”
Section: Discussionsupporting
confidence: 93%
“…Another line of evidence is that amplitudes of shoulder rotation are fine-tuned in response to the ratio value [1], [2], [4], [8], [9], [10], [11]. Such a functional relationship was observed even when participants were tested in a virtual reality [8], when running through apertures [4], or when older adults were tested [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Davis et al (2010) assessed how two adults performed the joint action of walking through an aperture. First, they established that a “shared” model, rather than an additive model, better predicted the critical boundary for the dyad's actual passage.…”
Section: Perceiving Others' Affordancesmentioning
confidence: 99%
“…For example, using functional magnetic resonance imaging (fMRI) Radke et al [2011] found increased brain activation in the medial prefrontal cortex following errors that had consequences for their co-actor in a cooperative computer gaming task. Similarly, when two people are asked to walk side-by-side through an aperture, they are sensitive to the fit required for the pair to pass through the aperture [Davis et al, 2010]. And we found in our previous study that when pairs cross a virtual road, as compared to singletons, they tend to act together, pick larger gaps, and synchronize their movement when crossing together [Jiang et al, 2016].…”
Section: Joint Action and Road Crossingmentioning
confidence: 96%